Clinical value of blood circulating (1→3)β-D-glucan in patients with suspected invasive fungal infection - V. P. Pirumovav; M. S. Gelfand (Онкогематология)
Invasive fungal infections (IFI) are a heterogeneous group of diseases, whose clinical significance is increased due to large number of cancerpatients, patients with aplastic anemia, congenital or acquired immunity defects. Morbidity and mortality due to fungal infection remain high, and the available diagnostic methods do not always allow timely detect and isolate infection pathogen. Microbiological and histological examination of biopsy material is the “gold standard” of IFI diagnostic, but in practice it is often associated with high risk for patients. Reliable nonculture methods of early IFI detection needed to improve current diagnostic and allowing an earlier decision of specific antifungal therapy. This article presents the advantages and limitations of one of these tests. In recent years, many articles and reviews about circulating (1→3)β-D-glucan (BDG) detection (major cell wall component of most pathogenic fungi) has appeared in the available literature. Despite that this test has a high diagnostic value, to recommend it for routine use in children with febrile neutropenia is premature. This test is less useful in making timely decision about diagnosis and start of antifungal therapy because of moderate sensitivity and specificity, the lack of evaluation criteria in children, late results (if detected in reference laboratory) and cost. BDG detection results can be interpreted only in conjunction with clinical course and data of routine laboratory and radiological methods.